The Influence of Service Quality and Sales Promotion on Customer Satisfaction at BeSt Sport Wisata Hotel Batu - Hanif, Hanif; Afandi, Yosi; Aini, Yulis Nurul (Sharia Business Management Department of STEBIS Bina Mandiri, 2025)
The rapid development of the tourism sector in Indonesia every year encourages business actors to better understand the needs of tourists. One of the main needs that must be fulfilled is the provision of comfortable and high-quality accommodation. The demand for lodging that can provide comfort as well as optimal service has become an important concern for the hospitality industry. This study aims to analyze the effect of service quality and sales promotion, both partially and simultaneously, on customer satisfaction at BeSt Sport Wisata Batu Hotel. This research is a quantitative study. Data were collected by distributing questionnaires to 80 respondents using a purposive sampling technique. The data were analyzed using multiple regression analysis. The analysis results show that service quality and sales promotion partially have a positive and significant effect on customer satisfaction. The results also show that simultaneously, service quality and sales promotion have a positive and significant effect on customer satisfaction. Both variables make a large contribution to satisfaction, while the remaining influence comes from other factors outside the study. Based on the research findings, it can be concluded that service quality has a significant partial effect on customer satisfaction, while sales promotion also has a significant effect. It is recommended that BeSt Sport Wisata Batu Hotel focus on improving service quality and maintaining sales promotion to build customer satisfaction.